2007
DOI: 10.1021/ja0685809
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Macroion−“Blackberry” Assembly−Macroion Transition with Continuously Adjustable Assembly Sizes in {Mo132} Water/Acetone Systems

Abstract: A complete, continuous transition from discrete macroions to blackberry structures, and then back to discrete macroions, is reported for the first time in the system of {Mo132}/water/acetone, with {Mo132} (full formula (NH4)42[Mo132O372(CH3COO)30(H2O)72].ca.300H2O.ca.10CH3COONH4) as the C60-like anionic polyoxomolybdate molecular clusters. Laser light scattering studies reveal the presence of the self-assembled {Mo132} blackberry structures in water/acetone mixed solvents containing 3 vol % to 70 vol % acetone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
150
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(171 citation statements)
references
References 48 publications
20
150
1
Order By: Relevance
“…[9][10][11][12] High nuclearity POM clusters based on Mo centers are well known; for example, {Mo 132 } and {Mo 154 } [13][14][15][16] clusters are synthetically accessible due to the occurrence of pentagonal and mixed-valence building blocks. [17][18][19] In contrast, the exploration of high nuclearity polyoxotungstate clusters has yielded different results with somewhat lower nuclearity isopolyoxotungstates: {W 34 } and {W 36 }, [20,21] and has been more limited since tungsten-based building blocks with pentagonal geometries have only very recently been accessed. [22][23] , [25,26] and most recently the synthesis of the spectacular {W 72 Fe 30 } "Keplerate".…”
mentioning
confidence: 99%
“…[9][10][11][12] High nuclearity POM clusters based on Mo centers are well known; for example, {Mo 132 } and {Mo 154 } [13][14][15][16] clusters are synthetically accessible due to the occurrence of pentagonal and mixed-valence building blocks. [17][18][19] In contrast, the exploration of high nuclearity polyoxotungstate clusters has yielded different results with somewhat lower nuclearity isopolyoxotungstates: {W 34 } and {W 36 }, [20,21] and has been more limited since tungsten-based building blocks with pentagonal geometries have only very recently been accessed. [22][23] , [25,26] and most recently the synthesis of the spectacular {W 72 Fe 30 } "Keplerate".…”
mentioning
confidence: 99%
“…Besides other interesting properties, molybdenum-and other transition metal-oxide based spherical and wheel-shaped polyoxometalates such as {Mo 132 }, {Mo 154 }, {Mo 72 X 30 ; X = Fe, V, Cr} and {W 48 P 8 -Cu 20 } are known to form spherical, single layered, hollow shell-like structures in solution [3][4][5][6]. It is remarkable that the POMs, which are in the size range of 2-3.6 nm, are able to self-assemble into shells of much larger length scales (ca.…”
Section: Introductionmentioning
confidence: 99%
“…To induce the formation of shell, the charge density on the POMs is regulated by either using mixture of solvents [3], or by varying the pH [13], or by the addition of oppositely charged surfactants [14]. These studies showed that charge density is an important parameter in controlling the radius of the shell.…”
Section: Introductionmentioning
confidence: 99%
“…[4] These building units are then able to undergo extended assembly processes, resulting in a variety of high nuclearity clusters that differ not only in terms of size and charge, [5] but also in shape and conformation, forming a range of supramolecular aggregates. [6] This structural flexibility is tantalizing in terms of the potential for real design but, given the plethora of species in solution, understanding and hence controlling self-assembly is extremely demanding. In this respect we have recently been employing electrospray ionization mass spectrometry (ESI-MS) in the characterization of the primary, secondary, and tertiary structures of POM clusters.…”
mentioning
confidence: 99%
“…One striking feature is that they tend to exchange TBA cations for protons, and occasionally, sodium cations, during the ionization process. The studies showed that the compounds can form assemblies of up to six clusters and 22 TBA cations resulting in [(X) 6 TBA 22 ] 4+ and nearly any smaller assembly that results in a maximum charge of + 4. Even larger supramolecular assemblies with higher charges might be possible, but we decided to limit our experiments to the m/z range up to 5000 Da, as obtaining sufficient intensity becomes difficult at higher mass values.…”
mentioning
confidence: 99%